2016
DOI: 10.1007/s00586-016-4655-5
|View full text |Cite
|
Sign up to set email alerts
|

Anterior cervical discectomy and fusion (ACDF) versus cervical disc arthroplasty (CDA) for two contiguous levels cervical disc degenerative disease: a meta-analysis of randomized controlled trials

Abstract: We can learn from this meta-analysis that the cervical disc arthroplasty (CDA) group is equivalent and in some aspects has more significant clinical outcomes than the ACDF group at two contiguous levels CDD.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
92
2
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 106 publications
(101 citation statements)
references
References 48 publications
5
92
2
2
Order By: Relevance
“…In two prospective, randomized, controlled trials comparing the same device with ACDF, similar mean ROM was reported at 5 years FU (10.2° and 9.3°) [22,26,31]. Likewise, this mean ROM was also in accordance with other mid-and long-term studies involving other devices which ranged from 6° to 13° [3,12,13,32]. A threshold of 2° has commonly been used to decide on the mobility of prostheses, possibly explaining why higher rates of mobility have been reported [21].…”
Section: Discussionsupporting
confidence: 86%
“…In two prospective, randomized, controlled trials comparing the same device with ACDF, similar mean ROM was reported at 5 years FU (10.2° and 9.3°) [22,26,31]. Likewise, this mean ROM was also in accordance with other mid-and long-term studies involving other devices which ranged from 6° to 13° [3,12,13,32]. A threshold of 2° has commonly been used to decide on the mobility of prostheses, possibly explaining why higher rates of mobility have been reported [21].…”
Section: Discussionsupporting
confidence: 86%
“…The cohort in this study was followed for at least 5 years with a follow-up of 94% and showed a statistically significant difference in rates of reoperations in total, advantageous for ACDF. This finding is deviant to results from most previously published RCTs and meta-analyzes showing lower rates of reoperations in the ADR groups [34][35][36][37][38]. The results in our study are supported by a study presented by Nandyala et al in 2014.…”
Section: Discussioncontrasting
confidence: 51%
“…Whereas some results indicated that TDR was significantly superior to ACDF 68 regarding several clinical outcomes, other results showed no significant difference between the two treatments 911 . Additionally, the clinical effectiveness among TDR using different replacements and ACDF using different implants remain unresolved.…”
Section: Introductionmentioning
confidence: 94%